Transcatheter aortic valve replacement in patients undergoing robotic totally endoscopic coronary artery bypass: A case series - Srivastava, Ankur; Smazil, Jennifer; Roark, Lauren; Shah, Hayla A.; Balkhy, Husam H.; Shah, Atman P. (Frontiers in Cardiovascular Medicine, 2022)
Transcatheter aortic valve replacement (TAVR) has been utilized to treat patients with symptomatic aortic stenosis (AS). Recent trials suggest comparable efficacy compared to surgical aortic valve replacement (SAVR). Robotic off-pump totally endoscopic coronary artery bypass graft surgery (TECAB) had been shown to be a minimally invasive revascularization strategy with clinical results comparable to traditional coronary artery bypass graft surgery (CABG). Traditionally, pre-surgical coronary evaluation is considered necessary to optimize coronary revascularization at the time of AVR. The 2020 ACC/AHA Guideline for the Management of Patients with Valvular Disease gives a moderate recommendation, based on limited data, for CABG at the time of AVR in patients with significant coronary artery disease (CAD). This paper presents two patients with known significant CAD awaiting robotic TECAB who were treated with TAVR, prior to surgical revascularization. Robotic TECAB is unique in that it offers patients the ability to have complete coronary revascularization without a sternotomy and with early ambulation, discharge, and recovery. The case series demonstrates a hybrid approach that offers complete sternotomy sparing cardiovascular care to treat severe symptomatic AS and CAD. Since patients with severe aortic stenosis are at high risk of developing cardiac arrest and cardiogenic shock upon induction of anesthesia, the ability to treat severe symptomatic AS with TAVR under conscious sedation prior to TECAB can be considered as a safe an effective treatment.